PENGARUH MOTIVASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT TRANSCAL SUNTECH INTERNATIOAL - Jurnal Akuntansi Barelang (JURNAL AKUNTANSI BARELANG, 2017)
This study aims to determine the effect of motivation, compensation and work environment on employee performance in PT Transcal Suntech International. This research method is using quantitative research method. The technique of collecting data is by distributing questionnaires to 171 respondents. Data were analyzed using test of validity, reliability, normality, multicollinearity, heterokedastisitas, multiple linear regression analysis, t test and F test. Test results of coefficient of determination Adjusted R Square shows that motivation, compensation and work environment variable are together providing 18.7 percent influence on employee performance variable. The results of this study indicate that partially motivation has no influence on employee performance, seen significant value 0.293 bigger than α value 0.05 and t value 1.054 smaller than t table 1.973 (H1 rejected), compensation has influence on employee performance because its significant value 0.000 smaller than α value 0.05 and t value 4.443 bigger than t table 1.973 (H2 accepted), work environment has influence on employee performance because its significant value 0.003 smaller than α value 0.05 and t value 3.000 bigger than t table 1.973 (H3 accepted), while motivation, compensation and work environment are simultaneously has significant effect on employee performance because its significant value 0.000 smaller than α value 0.05 and f value 14.062 bigger than f table 2.66 (H4 accepted).